Teaching wetlands in a global context: Geospatial learning aligned with Ramsar Convention and United Nations (UN) Sustainable Development Goals - Elena A. Mikhailova; Christopher J. Post; Davis G. Nelson; Hamdi A. Zurqani; Lili Lin; Zhenbang Hao (Wetlands Ecology and Management, 2026)
Teaching wetlands in a global context requires a pedagogical shift from local field observations to planetary systems analysis. This study proposes a teaching approach that integrates wetlands, analytical tools, policy frameworks, and a global purpose, which can be used in Earth science education. Laboratory exercise was developed and tested using wetlands (including a wetland of international importance and a Ramsar site: Congaree National Park) in the state of South Carolina (SC) in the United States of America (USA). Multidisciplinary students (wildlife biology, forestry, environmental and natural resources) engaged in active learning about subject matter definitions (e.g., hydric soils), used various geospatial analytical tools (e.g., Web Soil Survey), learned about Ramsar Convention (RC), and identified ecosystem services provided by wetlands for achieving the United Nations (UN) Sustainable Development Goals (SDGs). Results of two study years (2024 and 2025) were consistent, showing an increase in wetlands knowledge and applied analytical skills. The online quiz, taken by 113 students, had an average score of 9.3 out of 10. Students increased their knowledge of UN SDGs and ranked SDGs 6, 13, 14, and 15 as the most relevant SDGs to wetlands. A newly proposed teaching approach can be adopted worldwide, as most materials and tools are publicly available.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A cross-hatchery collaborative approach to developing hatchery techniques for the Atlantic sea scallop, Placopecten magellanicus - Sydney W. Avena; Anne Langston Noll; Christopher V. Davis; Cody Jourdet; Breanna Salter; Tessa Houston; Damian C. Brady (Aquaculture, 2026)

A performance comparison of mobile transect methods for heat and humidity prediction in complex urban environments - Andrew Robinson; Christopher Fuhrmann; Charles Konrad; Olivia M. Davis; Eric A. Kirk; David Parr (International Journal of Biometeorology, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

The effects of cadmium and high fructose diet on metabolic and reproductive health in female CD-1 mice - Victoria R. Adams; Janice A. Dye; Micheal G. Narotsky; Makala L. Moore; Helen H. Nguyen; Aubrey L. Sasser; Kaberi P. Das; Lillian F. Strader; Joseph P. Pancras; Donna Hill; Chloe Davis; Wanda C. Williams; et al. (Food and Chemical Toxicology, 2025)

Defining ‘abated’ fossil fuel and industrial process emissions - Christopher Bataille; Alaa Al Khourdajie; Heleen de Coninck; Kiane de Kleijne; Lars J. Nilsson; Igor Bashmakov; Steven J. Davis; Paul S. Fennell (Energy and Climate Change, 2025)

Best practices for producing actionable knowledge to inform fisheries management and conservation - Cosette Arseneault-Deraps; Raegan Davis; M. E. Cole MacLeod; Erin Wilson; Ben Aubrey; Alyssa Goodenough; Jamie C. Madden; Kevin A. Adeli; Christopher Cvitanovic; Nathan Young; Julie M. Hinderer; Elizabeth A. Nyboer; et al. (Environmental Biology of Fishes, 2025)

Congener Conflict: Invasive Barred Owl Landscape Use Across the Range of the Northern Spotted Owl - Julianna M. A. Jenkins; Natalie M. Rugg; Raymond J. Davis; Scott A. Gremel; Aaron Henderson; Edward Henson; Mark Higley; Holly D. Horan; Christopher McCafferty; Thomas Munger; David Press; Suzanne Reffler; et al. (Journal of Biogeography, 2025)
Aim To map the probability of landscape use of invading barred owls ( Strix varia ) across the range of the threatened northern spotted owl ( S. Occidentallis Caurina ) in the Pacific Northwest, USA , identifying environmental drivers of barred owl landscape use to inform targeted management interventions. Location Forests of the Pacific Northwest, USA. Taxon Barred Owl ( Strix varia ). Methods We deployed 4081 autonomous recording units ( ARUs ) within 1027 randomly selected long‐term monitoring sites consisting of 5‐km 2 hexagons in 2023. We processed audio recordings using convolutional neural networks to detect vocalisations. We applied single‐season occupancy models at both ARU station and hexagon scales to estimate barred owl landscape use and assess associations with environmental variables. Using top models, we mapped barred owl landscape use across the full US range of the northern spotted owl, an umbrella species for conservation of the pacific northwest old‐growth forest community. Results Barred owls were widely detected, with naïve occupancy at 86.8% at the 5‐km 2 hexagon scale. We observed regional variation, with the highest landscape use in the Oregon Coast region and lower landscape use in California regions and the Washington Eastern Cascades. Landscape use was positively associated with mature forest characteristics at both broad and fine scales and negatively associated with elevation and climatic water deficit. Cumulative detection probability exceeded 90% after 2 weeks at the hexagon scale and 4 weeks at the station scale, providing guidance for future barred owl monitoring efforts. Main Conclusions Our study reveals extensive, but not ubiquitous, barred owl distribution across the range of the northern spotted owl. The findings offer a decision‐support framework for prioritising targeted management actions, particularly in regions with lower rates of barred owl landscape use. The integration of passive acoustic monitoring and AI‐based detection demonstrates a scalable approach for invasive species monitoring and conservation planning to meet management objectives in dynamic forest landscapes.

Implementation of a Healthcare Implicit Bias Training across Three Oncology Care Settings - Dana Rosenberg; Teletia Taylor; Hannah Arem; Kimberly Davis; Carla Williams; Julie E. Bauman; Christopher J. King; Mandi L. Pratt-Chapman (Journal of Cancer Education, 2025)
The purpose of this study was to describe evaluation outcomes, including reach, satisfaction with training, and strategies to increase uptake of implicit bias training across three cancer centers in Washington, DC. From October 25, 2022, to March 29, 2023, oncology clinicians and staff were asked to complete an implicit bias training and post-training survey. Strategies used to increase training reach included identifying and preparing champions, identifying facilitators and barriers, promoting adaptation, and mandating completion. We quantitatively assessed satisfaction with training and self-reported learning outcomes and qualitatively explored impact of the training and how implementation strategies affected uptake. We reviewed open-text responses for feedback and insights from learners. At the suggestion of our champions, we pivoted from a five-hour training to a one-hour training to adapt to clinical team availability. The most successful strategies for increasing training uptake included reducing training length and personalized follow-up from institutional champions. One hundred eight of the 163 (66%) invited learners completed the training. Over 94% of learners agreed or strongly agreed that they met the training’s three learning objectives: describing implicit bias, providing examples of implicit bias in healthcare settings, and reflecting on one’s own biases. Learners’ open-ended responses described how training reaffirmed viewpoints for some learners while others became more aware of their biases. Implementing an implicit bias training across multiple care settings was successful in reaching our goal of 100 learners; however, reach varied by setting due to competing priorities and less champion influence at one institution.

Early loss of astrocyte p38α MAPK reduces hippocampal neuroinflammation, enhances synaptic strength, and increases non-synaptic mitochondrial uncoupling in female mice during non-pathological aging - Caleb S. Bailey; John C. Gant; Hilaree N. Frazier; Josh M. Morganti; Meggie C. Coleman; Verda A. Davis; Hemendra J. Vekaria; Patrick G. Sullivan; Christopher M. Norris; Linda J. Van Eldik; David J. Braun (GeroScience, 2025)
The p38 mitogen-activated protein kinase has a well-characterized role in modulation of inflammatory processes throughout the body. In the central nervous system, p38 is primarily studied within neurons and microglia, most commonly in the context of neurological insult. The present study was designed to determine its function in astrocytes during non-pathological aging. We generated a conditional knockout model in which a tamoxifen-inducible Aldh1l1 promoter drives Cre recombinase expression in mice with exon 1 of the p38α gene flanked by loxP sites. Knockout of astrocyte p38α was achieved via tamoxifen administration in young sexually mature mice at 3–4 months old. Animals were subsequently aged to 21–24 months prior to performing electrophysiological, immunohistochemical, and biochemical analyses. We found that early loss of astrocyte p38α was associated with a reduction in hippocampal neuroinflammation and concomitant enhancement of synaptic strength in aged female mice. In subsequent experiments in younger animals, the knockout reduced peripheral GFAP levels and increased non-synaptic mitochondrial uncoupling. These findings indicate that astrocyte p38α has wide-ranging effects on brain metabolism, inflammation, and synaptic function during the course of normal aging, including release of GFAP from the central nervous system to the periphery. Follow-up studies exploring the role of astrocyte p38α in various age-associated neuropathological contexts are warranted.

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Comparison of Crotalidae Immune F(ab’)2 (Equine) and Crotalidae Polyvalent Immune Fab (Ovine) at Establishing Control of Initial Envenomation Symptoms in Louisiana Agkistrodon Envenomations - Taylor Sanders; Christine Murphy; Greggory Davis; Christina Aspinwall; Lauren Theriot; Christopher McVicker; Thomas Arnold (Journal of Medical Toxicology, 2025)
Introduction Copperheads and cottonmouths are responsible for most snake envenomations in Louisiana. While the United States Food and Drug Administration has approved both Crotalidae polyvalent immune Fab (FabAV) and Crotalidae immune F(ab’) 2 (Fab2AV) for Agkistrodon envenomations, data is limited comparing their efficacies for this indication. Methods This is a retrospective study comparing FabAV to Fab2AV in the treatment of suspected Agkistrodon envenomations in Louisiana between April 2017 and October 2024. Cases identifying rattlesnakes were excluded. The primary outcome was the need for additional antivenom doses to achieve control after the initial antivenom dose. Results One hundred fifty-eight patients received FabAV or Fab2AV, with 100 cases meeting inclusion criteria. Fifty-seven patients received FabAV and 43 received Fab2AV. The snake was identified as copperhead in 48 cases, cottonmouth in 23, and unidentified in 29. In the FabAV cohort, the initial number of vials ranged from four to 12 with a median dose of four vials. Nine FabAV cases (16%) required additional vials for initial control after the first dose. In the Fab2AV cohort, all patients received 10 vials initially, with 24 cases (56%) requiring additional vials for initial control after the first dose. There was a significant difference in the percentage of patients requiring additional control vials between FabAV and Fab2AV. Conclusion In this cohort of suspected Agkistrodon envenomations, control with initial recommended dosing was more often achieved with FabAV compared to Fab2AV (84% vs. 44%). The results suggest potential benefit to hospitals stocking FabAV in Louisiana and possibly other Agkistrodon- predominant regions.

Comparing field-based microplastic observations with ocean circulation model outputs in estuarine surface waters along a human population gradient - Sarah M. Davis; Thomas Lawrence; Irene Andreu; Andrew J. Davies; Rory Maynard-Dean; Christopher Kincaid; Kelton W. McMahon; Brian Preziosi; Coleen C. Suckling (Marine Pollution Bulletin, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

The Greatest Extinction Event in 66 Million Years? Contextualising Anthropogenic Extinctions - Jack H. Hatfield; Bethany J. Allen; Tadhg Carroll; Christopher D. Dean; Shuyu Deng; Jonathan D. Gordon; Thomas Guillerme; James P. Hansford; Jennifer F. Hoyal Cuthill; Philip D. Mannion; Inês S. Martins; Alexander R. D. Payne; et al. (Global Change Biology, 2025)
Biological communities are changing rapidly in response to human activities, with the high rate of vertebrate species extinction leading many to propose that we are in the midst of a sixth mass extinction event. Five past mass extinction events have commonly been identified across the Phanerozoic, with the last occurring at the end of the Cretaceous, 66 million years ago (Ma). However, life on Earth has always changed and evolved, with most species ever to have existed now extinct. The question is, are human activities increasing the rate and magnitude of extinction to levels rarely seen in the history of life? Drawing on the literature on extinctions primarily over the last 66 million years (i.e., the Cenozoic), we ask: (1) what comparisons can meaningfully be drawn? and (2) when did the Earth last witness an extinction event on this scale? We conclude that, although challenging to address, the available evidence suggests that the ongoing extinction episode still falls a long way short of the devastation caused by the bolide impact 66 Ma, but that it has likely surpassed most other Cenozoic events in magnitude, with the possible exception of the Eocene–Oligocene transition (34 Ma), about which much uncertainty remains. Given the number of endangered and at‐risk species, the eventual magnitude of the current event will depend heavily on humanity's response and how we interact with the rest of the biosphere over the coming millennia.

Decreases in chimpanzee respiratory disease signs and enteric viral quantity following implementation of anthroponotic disease prevention protocols at a long-term research site - Jacob D. Negrey; Samuel Angedakin; Rachna B. Reddy; Aaron A. Sandel; Salmah Jombela; Erone Akamumpa; Christopher Aliganyira; Charles Birungi; Davis Kalunga; Brian Kamugyisha; Diana Kanweri; Godfrey Mbabazi; et al. (Biological Conservation, 2025)

Tracing Blue Carbon Flows Across Diverse Seascapes - Christopher J. Fulton; Diego R. Barneche; Kay Davis; Cal Faubel; Cecilia Pascelli; Julie Vercelloni; Shaun K. Wilson (Global Change Biology, 2025)
Plants occupying coastal ecosystems draw in carbon dioxide (CO 2 ) from the air and water around them during photosynthesis. A fraction of this CO 2 becomes fixed into plant biomass and can eventually contribute to the blue carbon pool—organic carbon (C org ) sequestered in slow‐turnover sinks. An important step in protecting and enhancing this natural carbon sequestration pathway is determining the relative contributions of different coastal plants to this blue carbon pool in durable sinks. We compiled a global dataset of coastal soil carbon measurements and used a Bayesian hierarchical meta‐regression model to explore the relative contribution of local (autochthonous) versus external (allochthonous) sources of C org in the soils beneath tidal saltmarsh, mangrove, and seagrass wetlands. We found most soil C org in coastal wetlands came from allochthonous sources, rather than the habitat‐forming plants. Managing climate‐resilient blue carbon seascapes, therefore, requires an awareness of this portfolio of contributors to soil carbon sequestration. However, study design aspects such as soil sampling depth, levels of sample replication, and the modeling approach used to trace C org can have pronounced effects on the estimated contributions of different carbon sources. We outline a roadmap for improving how we track the various drivers of soil carbon sequestration in diverse mosaics of coastal vegetation.

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Adsorption of MC-LR enabled by customizable 3D printed graphene-coated structures - Justin D. Puhnaty; Jacob M. Lalley; Alan J. Kennedy; Jaylen A. Davis; Angela M. Evans; Sarah Grace Zetterholm; Connor C. Clark; Jesse L. Roberts; Christopher S. Griggs; Benjamin S. Magbanua (Journal of Environmental Chemical Engineering, 2025)

The Cerebellar Neuropsychiatric Rating Scale in the Spinocerebellar Ataxias - Anna L. Burt; Maureen P. Daly; Janet C. Sherman; Jeremy D. Schmahmann; Susan L. Perlman; Liana S. Rosenthal; Sheng-Han Kuo; Tetsuo Ashizawa; Theresa Zesiewicz; Cameron Dietiker; Puneet Opal; Antoine Duquette; et al. (The Cerebellum, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Public perceptions of aquaculture in Maine: The role of place-based values - Emily Whitmore; Anne Langston Noll; Christopher Davis; Thomas Safford; Lawrence Hamilton (Aquaculture, 2025)

Mortality and diurnal temperature range in Virginia - Robert E. Davis; Owen Himmel; Parker K. Sims; Christopher M. Fuhrmann (International Journal of Biometeorology, 2025)
The relationship between diurnal temperature range (DTR) and daily mortality from 2005 to 2020 is examined for seven large metropolitan areas in Virginia using distributed lag non-linear models that control for temperature and humidity. The relative risk of mortality increases for very high DTR, and there is a short lag effect of several days. High risk DTR days are rare, typically occurring less than 1% of the time at most locations. These days primarily occur in spring and are characterized by high pressure and low humidity that allow overnight temperatures to drop substantially. High DTR days are often associated with elevated respiratory and cardiovascular mortality and tend to impact the elderly. The similarity between the mortality response to high DTR and that of high temperatures alone, coupled with the lack of clear physiological underpinnings, challenges the notion that these responses are independent. The prevalent spring peak in dangerous DTR days suggests that lack of acclimatization to hot and humid conditions may impose strain on the cardiovascular and respiratory systems.

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Working the ground game: How Maine shellfish and seaweed farmers are building social license to operate - Emily Whitmore; Christopher Davis; Thomas Safford (Aquaculture, 2025)

Science × art: spotlighting unconventional collaborations - Charles C. Davis; Jackson Kehoe; Anna C. Knaap; Christopher D.M. Atkins (Trends in Ecology & Evolution, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Bridging the gap: exploring consumer knowledge, perceptions, and willingness to pay for aquaponics products across the UK - Joshua Davis; Rose R. Murray; Rosemary Crichton; Finn Starkey; Christopher Cammies (Aquaculture International, 2025)
Aquaponics (a sub-field of integrated agri-aquacultural practices (IAAS)) has emerged as a novel approach to combat global food security, reduce soil erosion and nutrient loss, and mitigate agronomic greenhouse gas (GHG) emissions. However, little remains known of potential consumer markets. Despite recent research throughout Europe, Central America, Australia, and the Middle East, this work represents the first large-scale evaluation of UK consumer understanding, assessment, and willingness to pay (WTP) for aquaponic products. Following analysis of 588 survey responses, we identify environmental awareness and green consumption, recognition of common UK eco-labels and sector-specific certification schemes, and consumer perceptions of aquaponics compared to conventional, locally sourced, and organic food production. Initially, 44% of survey respondents were familiar with aquaponics, with familiarity positively influenced by age and level of education. After presenting a definition of aquaponics (detailing its use and commonly cited socio-environmental benefits), consumer perceptions were mixed, with respondents broadly favourable to the practice despite uncertainty. Over 43% of consumers were willing to pay an associated price premium for aquaponic produce (valued, on average, as a 23% price increase over conventional alternatives). This willingness to pay was statistically in line with the organic market premiums and independent of prior familiarity with aquaponics as a food production system. These findings suggest a sizable consumer market for aquaponic produce and public interest in its sustainability benefits. Tailored marketing strategies could position aquaponic produce competitively alongside organic and environmentally friendly alternatives (irrespective of certification/eco-labelling), ensuring the long-term economic viability of the emerging aquaponics industry.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Long-term patterns and trends in water column biogeochemistry in a changing environment - Paul Julian; James W. Fourqurean; Stephen E. Davis; Donatto Surratt; Evelyn E. Gaiser; John S. Kominoski; Tiffany G. Troxler; Joseph N. Boyer; Serge Thomas; Henry O. Briceño; Christopher J. Madden; Enrique Montes; et al. (Estuarine, Coastal and Shelf Science, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Oxadiazole derivatives as stable anolytes for >3 V non-aqueous redox flow battery - Kate A. Jesse; Sergio Diaz-Abad; Christopher E. Van Pelt; Emily Pentzer; Benjamin L. Davis; Sandip Maurya (Chemical Engineering Journal, 2024)

Research and educational applications of the Aerojet General Nucleonics 201-M at the University of New Mexico - Rowdy Davis; Christopher M. Perfetti; Robert D. Busch; Larry L. Wetzel; Carl A. Willis (Annals of Nuclear Energy, 2024)

Ten-Year Response of Riparian-Associated Songbirds to Implementation of Streamside Management Zones in Watershed-Scale Harvests in the Appalachian Mountains - Zachary J Hackworth; John J Cox; Jeffery L Larkin; Wendy Leuenberger; Joshua M Felch; Allison G Davis; Christopher D Barton (Journal of Forestry, 2024)
Streamside management zones (SMZs) are regulated components of actively managed forests in the eastern United States, but width and overstory retention requirements vary widely among states. Within watershed-scale harvests, we evaluated the relative abundances of three riparian-associated songbirds (Acadian flycatcher, Empidonax virescens; blue-headed vireo, Vireo solitarius; and Louisiana waterthrush, Parkesia motacilla) near Appalachian headwater streams receiving three SMZ treatments representative of a range of current state SMZ regulations in the eastern United States. Prior to harvest, all species were relatively abundant near all stream types, including ephemerals. Abundances of all species were largely similar among SMZ treatments at 3 years and 10 years postharvest and were higher along streams with greater residual canopy cover within 100 m. Forested SMZs as prescribed by current regulations can sustain these species in managed forests up to 10 years postharvest, but abundance appears to be driven largely by canopy cover retention in adjacent stands. Managing habitat for riparian-associated songbirds in harvested watersheds will require expanding the extent of focus beyond the local stream corridor to include consideration of silvicultural systems that retain greater canopy cover in surrounding forests. Where conservation of riparian-associated songbirds is a management objective, SMZ protection should be extended to all streams. Study Implications: The results of this study suggest that forested streamside management zones (SMZs) mandated by contemporary best management practices (BMPs) in Kentucky and other eastern US states can sustain similar abundances of three riparian-associated songbirds in managed watersheds up to 10 years after harvest. Overstory retention in SMZs along perennial and intermittent streams is common across the eastern United States, but state BMPs rarely require retention along ephemeral streams. Target songbird species occupied forests along all stream types prior to harvest, and their postharvest abundances were positively associated with canopy retention within 100 m of streams. If long-term occupancy of managed stands by riparian-associated songbirds is an objective, we recommend using SMZs around all streams, including ephemerals, and implementing at least moderate-retention silvicultural systems in areas within 100 m of streams.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Differences in internal sedimentologic and biotic structure between natural, managed, and constructed coastal foredunes - Elizabeth H. Davis; Christopher J. Hein; Nicholas Cohn; Andrew E. White; Julie C. Zinnert (Geomorphology, 2024)

A critical re‐analysis of constraints on the timing and rate of Laurentide Ice Sheet recession in the northeastern United States - Christopher T. Halsted; Paul R. Bierman; Jeremy D. Shakun; P. Thompson Davis; Lee B. Corbett; Jason S. Drebber; John C. Ridge (Journal of Quaternary Science, 2024)
We review geochronological data relating to the timing and rate of Laurentide Ice Sheet recession in the northeastern United States and model ice margin movements in a Bayesian framework using compilations of previously published organic 14 C ( n = 133) and in situ cosmogenic 10 Be ( n = 95) ages. We compare the resulting method‐specific chronologies with glacial varve records that serve as independent constraints on the pace of ice recession to: (1) construct a synthesis of deglacial chronology throughout the region; and (2) assess the accuracy of each chronometer for constraining the timing of deglaciation. Near the Last Glacial Maximum terminal moraine zone, 10 Be and organic 14 C ages disagree by thousands of years and limit determination of the initial recession to a date range of 24–20 ka. We infer that 10 Be inherited from pre‐glacial exposure adds 2–6 kyr to many exposure ages near the terminal moraines, whereas macrofossil 14 C ages are typically 4–8 kyr too young due to a substantial lag between ice recession and sufficient organic material accumulation for dating in some basins. Age discrepancies between these chronometers decrease with distance from the terminal moraine, due to less 10 Be inherited from prior exposure and a reduced lag between ice recession and organic material deposition. 14 C and 10 Be ages generally agree at locations more than 200 km distal from the terminal moraines and suggest a mostly continuous history of ice recession throughout the region from 18 to 13 ka with a variable pace best documented by varves.

Validation of octane hyperboosting phenomenon in prenol and structurally related olefinic alcohols - Alexander Landera; Eric Monroe; Nicholas R. Myllenbeck; Joseph Carlson; Anthe George; Christopher P. Kolodziej; Alexander Hoth; Jon Luecke; Gina M. Fioroni; Ryan W. Davis (Fuel, 2023)

Production of secondary metabolites in regenerated Southern wormwood (Artemisia abrotanum L.) under various experimental conditions - Adna Alihodzic; Jimmy Davis; Christopher Roberts; Sally Henrie; Mark Bolyard (In Vitro Cellular & Developmental Biology - Plant, 2023)

Post-orogenic exhumation triggers gold mineralization in the Trans-Hudson orogen: New geochronology results from the Lynn Lake greenstone belt, Manitoba, Canada - Christopher J.M. Lawley; David A. Schneider; Alfredo Camacho; Christopher R.M. McFarlane; William J. Davis; Xue-Ming Yang (Precambrian Research, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Task impairment: A novel approach for assessing impairment during exploration-class spaceflight missions - William Fernandez; Dana Levin; Jon G. Steller; Eric Kerstman; Jay Lemery; Christopher Zahner; Hillary E. Davis; Kris Lehnhardt; Benjamin Easter; Amy J. Kreykes (Journal of Space Safety Engineering, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Coherence among Oregon Coast coho salmon populations highlights increasing relative importance of marine conditions for productivity - Melanie J. Davis; James Anthony; Eric J. Ward; Julie Firman; Christopher Lorion (Fisheries Oceanography, 2023)
Anadromous fishes, such as Pacific salmon, spend portions of their life cycle in freshwater and marine systems, thus rendering them susceptible to a variety of natural and anthropogenic stressors. These stressors operate at different spatiotemporal scales, whereby freshwater conditions are more likely to impact single populations or subpopulations, while marine conditions are more likely to act on entire evolutionarily significant units (ESUs). Coherence in population parameters like survival and productivity can therefore serve as an indicator of relative influence. The goal of this study was to elucidate scale‐dependent shifts in Oregon Coast coho salmon productivity. We used a multivariate state‐space approach to analyze almost 60 years of stock‐recruitment data for the Oregon Coast ESU. Analyses were conducted separately for time periods prior to and after 1990 to account for improvements in abundance estimation methods and significant changes in conservation and management strategies. Prior to 1990, productivity declined for most Oregon Coast populations, especially through the 1980s. From 1990–onward, coherence increased, and trends tracked closely with the North Pacific Gyre Oscillation (NPGO). The latter period is associated with reductions in harvest rates and hatchery production such that the relative influence of the marine environment may have grown more apparent following the removal of these stressors. Furthermore, the link between productivity and NPGO is consistent with trends observed for several other Pacific salmon ESUs. If Oregon Coast coho salmon populations become more synchronous, managers can expect to face new challenges driven by reductions in the population portfolio effect and increasingly variable marine conditions due to climate change.

Highly socially vulnerable communities exhibit disproportionately increased viral loads as measured in community wastewater - William M. Baldwin; Robert D. Dayton; Aaron W. Bivins; Rona S. Scott; Andrew D. Yurochko; John A. Vanchiere; Terry Davis; Connie L. Arnold; Jose.E.T. Asuncion; Mohammad A.N. Bhuiyan; Brandon Snead; William Daniel; et al. (Environmental Research, 2023)

Planktic foraminifera iodine/calcium ratios from plankton tows - Helge A. Winkelbauer; Babette A. A. Hoogakker; Rosie J. Chance; Catherine V. Davis; Christopher J. Anthony; Juliane Bischoff; Lucy J. Carpenter; Simon R. N. Chenery; Elliott M. Hamilton; Philip Holdship; Victoria L. Peck; Alex J. Poulton; et al. (Frontiers in Marine Science, 2023)
Planktic foraminifera test iodine to calcium ratios represent an emerging proxy method to assess subsurface seawater oxygenation states. Several core-top studies show lower planktic foraminifera I/Ca in locations with oxygen depleted subsurface waters compared to well oxygenated environments. The reasoning behind this trend is that only the oxidized species of iodine, iodate, is incorporated in foraminiferal calcite. The I/Ca of foraminiferal calcite is thought to reflect iodate contents in seawater. To test this hypothesis, we compare planktic foraminifera I/Ca ratios, obtained from plankton tows, with published and new seawater iodate concentrations from 1) the Eastern North Pacific with extensive oxygen depletion, 2) the Benguela Current System with moderately depleted oxygen concentrations, and 3) the well oxygenated North and South Atlantic. We find the lowest I/Ca ratios (0.07 µmol/mol) in planktic foraminifera retrieved from the Eastern North Pacific, and higher values for samples (up to 0.72 µmol/mol) obtained from the Benguela Current System and North and South Atlantic. The I/Ca ratios of plankton tow foraminifera from environments with well oxygenated subsurface waters, however, are an order of magnitude lower compared to core-tops from similarly well-oxygenated regions. This would suggest that planktic foraminifera gain iodine post-mortem, either when sinking through the water column, or during burial.

Estimates of broadband upwelling irradiance from GOES-16 ABI - Kevin McCloskey; Sixing Chen; Vincent R. Meijer; Joe Yue-Hei Ng; Geoff Davis; Carl Elkin; Christopher Van Arsdale; Scott Geraedts (Remote Sensing of Environment, 2023)

An Experimental Platform to Study Wind, Hydrodynamic, and Biochemical Conditions in the Littoral Zone During Extreme Coastal Storms - Brian Phillips; Forrest Masters; Britt Raubenheimer; Maitane Olabarrieta; Elise Morrison; Pedro Fernández-Cabán; Christopher Ferraro; Justin Davis; Taylor Rawlinson; Michael Rodgers (Oceanography, 2023)
Tropical cyclones and other extreme coastal storms cause widespread interruption and damage to meteorological and hydrological measurement stations exactly when researchers need them most. There is a longstanding need to collect collocated and synchronized measurements in areas where storms severely damage civil/coastal infrastructure. To fill this observational gap, researchers led by author Masters developed a state-of-the-art monitoring station called a “Sentinel.” Sentinels are intended for temporary installation on the beach between the mean tidal datum and the sand dunes and are engineered to operate in and measure extreme wind, storm surge, wave, and hazardous water quality conditions. They are envisioned as a shared-use resource—a hardened IoT (Internet of Things) platform set up in the right place at the right time to study wind and wave loads, coastal erosion and morphology changes, water quality, and other processes during extreme coastal storms.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

A Climate-Mediated Shift in the Estuarine Habitat Mosaic Limits Prey Availability and Reduces Nursery Quality for Juvenile Salmon - Melanie J. Davis; Isa Woo; Christopher S. Ellings; Sayre Hodgson; David A. Beauchamp; Glynnis Nakai; Susan E. W. De La Cruz (Estuaries and Coasts, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Importance of equitable cost sharing in the Convention on Biological Diversity's protected area agenda - Keila Stark; Vanessa Adams; Christopher J. Brown; Alienor Chauvenet; Katrina Davis; Edward T. Game; Benjamin S. Halpern; John Lynham; Bonnie Mappin; Kim Selkoe; James E. M. Watson; Hugh P. Possingham; et al. (Conservation Biology, 2022)

Caffeine and attentional control: improved and impaired performance in healthy older adults and Parkinson’s disease according to task demands - Kanch Sharma; Sean James Fallon; Thomas Davis; Scott Ankrett; Greg Munro; Gary Christopher; Elizabeth Coulthard (Psychopharmacology, 2022)
Introduction Caffeine is frequently consumed to boost goal-directed attention. These procognitive effects may occur due to the adenosine-mediated enhancement of monoamines, such as dopamine, after caffeine administration. As such, caffeine’s beneficial effects may be altered in conditions such as Parkinson’s disease (PD). However, whether caffeine improves cognition, and at what cost, has not been experimentally established in patients with neurodegenerative disease. Methods Single-dose trials to probe cognitive effects of caffeine are often confounded by short-term caffeine abstinence which conflates caffeine’s effects with treatment of withdrawal. Using a placebo controlled, blinded, randomised trial design, we assessed the effect of 100 mg of caffeine across well-established tasks (Choice reaction time, Stroop Task and Rapid Serial Visual Presentation Task; RSVP) that probe different aspects of attention in PD patients ( n = 24) and controls ( n = 44). Critically, participants withdrew from caffeine for a week prior to testing to eliminate the possibility that withdrawal reversal explained any cognitive benefit. Results Caffeine administration was found to reduce the overall number of errors in patients and controls on the Stroop ( p = .018, η 2 p = .086) and Choice reaction time ( p < . 0001, η 2 p = .588) tasks, but there was no specific effect of caffeine on ignoring irrelevant information in the Stroop task. On the RSVP task, caffeine improved dual item accuracy ( p = .037) but impaired single item accuracy ( p = .044). Across all tasks, there was little evidence that caffeine has different effects in PD participants and controls. Conclusion When removing withdrawal effects as a factor, we demonstrate caffeine has beneficial effects on selective attention but is a double-edge sword for visual temporal attention and would need careful targeting to be clinically useful.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Walking while Parasitized: Effects of a Naturally-Occurring Nematode on Locomotor Activity of Horned Passalus Beetles - Andrew K. Davis; Christian Hurd; Christopher Brandon; David Vasquez (Journal of Insect Behavior, 2021)

Understanding quality and equity: patient experiences with care in older adults diagnosed with hematologic malignancies - Alex Fauer; Sung Won Choi; Lauren P. Wallner; Matthew A. Davis; Christopher R. Friese (Cancer Causes & Control, 2021)

Reintroducing extirpated herbivores could partially reverse the late Quaternary decline of large and grazing species - Simon D. Schowanek; Matt Davis; Erick J. Lundgren; Owen Middleton; John Rowan; Rasmus Ø. Pedersen; Daniel Ramp; Christopher J. Sandom; Jens‐Christian Svenning (Global Ecology and Biogeography, 2021)
Aim Reinstating large, native herbivores is an essential component of ecological restoration efforts, as these taxa can be important drivers of ecological processes. However, many herbivore species have gone globally or regionally extinct during the last 50,000 years, leaving simplified herbivore assemblages and trophically downgraded ecosystems. Here, we discuss to what extent trophic rewilding can undo these changes by reinstating native herbivores. Location Global. Time period We report functional trait changes from the Late Pleistocene to the present, and estimated trait changes under future scenarios. Major taxa studied Wild, large (≥ 10 kg), terrestrial, mammalian herbivores. Methods We use a functional trait dataset containing all late Quaternary large herbivores ≥ 10 kg to look at changes in the body mass and diet composition of herbivore assemblages, a proxy for species’ ecological effects. First, we assess how these traits have changed from the Late Pleistocene to the present. Next, we quantify how the current body mass and diet composition would change if all extant, wild herbivores were restored to their native ranges (and if no functional replacements were used), exploring scenarios with different baselines. Results Defaunation has primarily removed large and grazing herbivores. Reinstating extant herbivores across their native ranges would reverse these changes, especially when reinstating them to their prehistoric distributions. It would partially restore herbivore body mass and diet composition to pre‐anthropogenic conditions. However, in the absence of complementary interventions (e.g., introducing functional replacements), many herbivore assemblages would remain down‐sized and browser dominated, relative to pre‐anthropogenic conditions. Main conclusions Many terrestrial herbivore assemblages—and hence ecosystems—would remain trophically downgraded, even after bringing back all extant, native herbivores. Therefore, complementary interventions would be required to achieve complete functional restoration. Nevertheless, our findings suggest that reintroducing the remaining native herbivores would diversify the herbivory and disturbances of herbivore assemblages.

Molecular sexing is a viable alternative to probing for determining sex in the imperiled Louisiana Pine Snake (Pituophis ruthveni) - Aron D. Katz; Sarah Pearce; Christopher Melder; Jinelle H. Sperry; Mark A. Davis (Conservation Genetics Resources, 2020)

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Identifying archaeological evidence of past earthquakes in a contemporary disaster scenario: case studies of damage, resilience and risk reduction from the 2015 Gorkha Earthquake and past seismic events within the Kathmandu Valley UNESCO World Heritage Property (Nepal) - Christopher Davis; Robin Coningham; Kosh Prasad Acharya; Ram Bahadur Kunwar; Paolo Forlin; Kai Weise; Prem Nath Maskey; Anie Joshi; Ian Simpson; David Toll; Sean Wilkinson; Paul Hughes; et al. (Journal of Seismology, 2020)
The 2015 Gorkha Earthquake was a humanitarian disaster but also a cultural catastrophe that damaged and destroyed historic monuments across Nepal, including those within the Kathmandu Valley UNESCO World Heritage Property. In the rush to rebuild, traditionally constructed foundations are being removed and replaced with modern materials without assessments of whether these contributed to the collapse of a monument. Generally undertaken without scientific recording, these interventions have led to the irreversible destruction of earlier subsurface phases of cultural activity and the potential loss of evidence for successful traditional seismic adaptations and risk reduction strategies, with no research into whether modern materials, such as concrete and steel, would offer enhanced resilience. In response to this context, multidisciplinary post-disaster investigations were undertaken between 2015 and 2018, including archaeological excavation, geophysical survey, geoarchaeological analysis, linked to architectural and engineering studies, to begin to evaluate and assess the damage to, and seismic adaptations of, historic structures within Nepal’s Kathmandu Valley. Where possible, we draw on archaeoseismological approaches for the identification and classification of Earthquake Archaeological Effects (EAEs) at selected monuments damaged by the 2015 Gorkha Earthquake. Lessons learned from evidence of potential weaknesses, as well as historic ‘risk-sensitive tactics’ of hazard reduction within monuments, are now being incorporated into reconstruction and rehabilitation initiatives alongside the development of methods for the protection of heritage in the face of future earthquakes.

Yellowstone Lake Ecosystem Restoration: A Case Study for Invasive Fish Management - Todd M. Koel; Jeffery L. Arnold; Patricia E. Bigelow; Travis O. Brenden; Jeffery D. Davis; Colleen R. Detjens; Philip D. Doepke; Brian D. Ertel; Hayley C. Glassic; Robert E. Gresswell; Christopher S. Guy; Drew J. MacDonald; et al. (Fishes, 2020)
Invasive predatory lake trout Salvelinus namaycush were discovered in Yellowstone Lake in 1994 and caused a precipitous decrease in abundance of native Yellowstone cutthroat trout Oncorhynchus clarkii bouvieri. Suppression efforts (primarily gillnetting) initiated in 1995 did not curtail lake trout population growth or lakewide expansion. An adaptive management strategy was developed in 2010 that specified desired conditions indicative of ecosystem recovery. Population modeling was used to estimate effects of suppression efforts on the lake trout and establish effort benchmarks to achieve negative population growth (λ 46,800 100-m net nights; this effort level was achieved in 2012 and led to a reduction in lake trout biomass. Total lake trout biomass declined from 432,017 kg in 2012 to 196,675 kg in 2019, primarily because of a 79% reduction in adults. Total abundance declined from 925,208 in 2012 to 673,983 in 2019 but was highly variable because of recruitment of age-2 fish. Overall, 3.35 million lake trout were killed by suppression efforts from 1995 to 2019. Cutthroat trout abundance remained below target levels, but relative condition increased, large individuals (> 400 mm) became more abundant, and individual weights doubled, probably because of reduced density. Continued actions to suppress lake trout will facilitate further recovery of the cutthroat trout population and integrity of the Yellowstone Lake ecosystem.

Energetic Carrying Capacity of Submersed Aquatic Vegetation in Semi-Permanent Wetlands Important to Waterfowl in the Upper Midwest - Margaret C. Gross; Joseph D. Lancaster; John W. Simpson; Brendan T. Shirkey; Sarah E. McClain; Christopher N. Jacques; J. Brian Davis; Heath M. Hagy (Wetlands, 2020)

Effects of Saltwater Pulses on Soil Microbial Enzymes and Organic Matter Breakdown in Freshwater and Brackish Coastal Wetlands - Shelby Servais; John S. Kominoski; Carlos Coronado-Molina; Laura Bauman; Stephen E. Davis; Evelyn E. Gaiser; Stephen Kelly; Christopher Madden; Viviana Mazzei; David Rudnik; Fabiola Santamaria; Fred H. Sklar; et al. (Estuaries and Coasts, 2020)

Experimental, numerical and field study investigating a heritage structure collapse after the 2015 Gorkha earthquake - Ashutosh Kumar; Paul N. Hughes; Vasilis Sarhosis; David Toll; Sean Wilkinson; Robin Coningham; Kosh Prasad Acharya; Kai Weise; Annie Joshi; Christopher Davis; Ram Bahadur Kunwar; Prem Nath Maskey (Natural Hazards, 2020)
This paper presents an investigation of the collapse of a 325-year-old multi-tiered heritage temple during the 2015 Gorkha earthquake in Kathmandu, Nepal. The research comprises a reconnaissance survey followed by a geotechnical investigation and numerical back-analysis carried out to understand the potential causes of the collapse. The assessment of the structural configuration of the temple indicated seismic vulnerability in the design due to the presence of discontinuous columns over the height of the temple and age-weakened bonding in the masonry walls. The geotechnical investigation revealed the presence of competent soil strata at the location, assisting the survey which indicated no differential or excessive settlement in the foundation. A series of cyclic triaxial tests were conducted on samples recovered during the geotechnical investigation to determine dynamic behaviour of the soil. Further, dynamic analysis of the plinth of the temple under the recorded acceleration–time history indicated a maximum drift percentage of 1.4% and residual relative displacement of 32 mm suggesting the potential reason behind the collapse. The output of this research will support seismic rehabilitation of ancient structures within World Heritage sites across Nepal and effective action plans to safeguard them against future earthquake hazard.

Evaluation of environmental DNA to detect Sistrurus catenatus and Ophidiomyces ophiodiicola in crayfish burrows - Sarah J. Baker; Matthew L. Niemiller; Andrew J. Stites; Kurt T. Ash; Mark. A. Davis; Michael J. Dreslik; Christopher A. Phillips (Conservation Genetics Resources, 2020)

Experimental Saltwater Intrusion Drives Rapid Soil Elevation and Carbon Loss in Freshwater and Brackish Everglades Marshes - Sean P. Charles; John S. Kominoski; Tiffany G. Troxler; Evelyn E. Gaiser; Shelby Servais; Benjamin J. Wilson; Stephen E. Davis; Fred H. Sklar; Carlos Coronado-Molina; Christopher J. Madden; Steve Kelly; David T. Rudnick (Estuaries and Coasts, 2019)

A Mosaic of Estuarine Habitat Types with Prey Resources from Multiple Environmental Strata Supports a Diversified Foraging Portfolio for Juvenile Chinook Salmon - Isa Woo; Melanie J. Davis; Christopher S. Ellings; Sayre Hodgson; John Y. Takekawa; Glynnis Nakai; Susan E. W. De La Cruz (Estuaries and Coasts, 2019)

Neuroprotective activity of leukemia inhibitory factor is relayed through myeloid zinc finger-1 in a rat model of stroke - Stephanie M. Davis; Lisa A. Collier; Elspeth A. Foran; Christopher C. Leonardo; Craig T. Ajmo; Keith R. Pennypacker (Metabolic Brain Disease, 2019)

How commercial fishing effort is managed - Christopher M. Anderson; Melissa J. Krigbaum; Martin C. Arostegui; Megan L. Feddern; John Zachary Koehn; Peter T. Kuriyama; Christina Morrisett; Caitlin I. Allen Akselrud; Melanie J. Davis; Courtney Fiamengo; Ava Fuller; Qi Lee; et al. (Fish and Fisheries, 2019)
Wild capture fisheries produce 90 million tonnes of food each year and have the potential to provide sustainable livelihoods for nearly 40 million people around the world ( http://www.fao.org/3/a-i5555e.pdf ). After decades of overfishing since industrialization, many global fish stocks have recovered, a change brought about through effective management. We provide a synthetic overview of three approaches that managers use to sustain stocks: regulating catch and fishing mortality, regulating effort and regulating spatial access. Within each of these approaches, we describe common restrictions, how they alter incentives to change fishing behaviour, and the resultant ecological, economic and community‐level outcomes. For each approach, we present prominent case‐studies that illustrate behaviour and the corresponding performance. These case‐studies show that sustaining target stocks requires a hard limit on fishing mortality under most conditions, but that additional measures are required to generate economic benefits. Different systems for allocation allow stakeholder communities to strike a locally acceptable balance between profitability and employment.

The climate, the fuel and the land use: Long‐term regional variability of biomass burning in boreal forests - Chiara Molinari; Veiko Lehsten; Olivier Blarquez; Christopher Carcaillet; Basil A. S. Davis; Jed O. Kaplan; Jennifer Clear; Richard H. W. Bradshaw (Global Change Biology, 2018)
The influence of different drivers on changes in North American and European boreal forests biomass burning (BB) during the Holocene was investigated based on the following hypotheses: land use was important only in the southernmost regions, while elsewhere climate was the main driver modulated by changes in fuel type. BB was reconstructed by means of 88 sedimentary charcoal records divided into six different site clusters. A statistical approach was used to explore the relative contribution of (a) pollen‐based mean July/summer temperature and mean annual precipitation reconstructions, (b) an independent model‐based scenario of past land use (LU), and (c) pollen‐based reconstructions of plant functional types (PFTs) on BB. Our hypotheses were tested with: (a) a west‐east northern boreal sector with changing climatic conditions and a homogeneous vegetation, and (b) a north‐south European boreal sector characterized by gradual variation in both climate and vegetation composition. The processes driving BB in boreal forests varied from one region to another during the Holocene. However, general trends in boreal biomass burning were primarily controlled by changes in climate (mean annual precipitation in Alaska, northern Quebec, and northern Fennoscandia, and mean July/summer temperature in central Canada and central Fennoscandia) and, secondarily, by fuel composition (BB positively correlated with the presence of boreal needleleaf evergreen trees in Alaska and in central and southern Fennoscandia). Land use played only a marginal role. A modification towards less flammable tree species (by promoting deciduous stands over fire‐prone conifers) could contribute to reduce circumboreal wildfire risk in future warmer periods.

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Correction to: Nest predation and the influence of habitat structure on nest predation of Wood Warbler Phylloscopus sibilatrix, a ground-nesting forest passerine - Paul E. Bellamy; Malcolm D. Burgess; John W. Mallord; Andrew Cristinacce; Christopher J. Orsman; Tony Davis; Philip V. Grice; Elisabeth C. Charman (Journal of Ornithology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Evaluation of eDNA for groundwater invertebrate detection and monitoring: a case study with endangered Stygobromus (Amphipoda: Crangonyctidae) - Matthew L. Niemiller; Megan L. Porter; Jenna Keany; Heather Gilbert; Daniel W. Fong; David C. Culver; Christopher S. Hobson; K. Denise Kendall; Mark A. Davis; Steven J. Taylor (Conservation Genetics Resources, 2018)

Nitrate uptake in an agricultural stream estimated from high-frequency, in-situ sensors - Christopher S. Jones; Sea-won Kim; Thomas F. Wilton; Keith E. Schilling; Caroline A. Davis (Environmental Monitoring and Assessment, 2018)

Nest predation and the influence of habitat structure on nest predation of Wood Warbler Phylloscopus sibilatrix, a ground-nesting forest passerine - Paul E. Bellamy; Malcolm D. Burgess; John W. Mallord; Andrew Cristinacce; Christopher J. Orsman; Tony Davis; Philip V. Grice; Elisabeth C. Charman (Journal of Ornithology, 2018)

Equity trade‐offs in conservation decision making - Elizabeth A. Law; Nathan J. Bennett; Christopher D. Ives; Rachel Friedman; Katrina J. Davis; Carla Archibald; Kerrie A. Wilson (Conservation Biology, 2018)
Conservation decisions increasingly involve multiple environmental and social objectives, which result in complex decision contexts with high potential for trade‐offs. Improving social equity is one such objective that is often considered an enabler of successful outcomes and a virtuous ideal in itself. Despite its idealized importance in conservation policy, social equity is often highly simplified or ill‐defined and is applied uncritically. What constitutes equitable outcomes and processes is highly normative and subject to ethical deliberation. Different ethical frameworks may lead to different conceptions of equity through alternative perspectives of what is good or right. This can lead to different and potentially conflicting equity objectives in practice. We promote a more transparent, nuanced, and pluralistic conceptualization of equity in conservation decision making that particularly recognizes where multidimensional equity objectives may conflict. To help identify and mitigate ethical conflicts and avoid cases of good intentions producing bad outcomes, we encourage a more analytical incorporation of equity into conservation decision making particularly during mechanistic integration of equity objectives. We recommend that in conservation planning motivations and objectives for equity be made explicit within the problem context, methods used to incorporate equity objectives be applied with respect to stated objectives, and, should objectives dictate, evaluation of equity outcomes and adaptation of strategies be employed during policy implementation.

Range position and climate sensitivity: The structure of among‐population demographic responses to climatic variation - Staci M. Amburgey; David A. W. Miller; Evan H. Campbell Grant; Tracy A. G. Rittenhouse; Michael F. Benard; Jonathan L. Richardson; Mark C. Urban; Ward Hughson; Adrianne B. Brand; Christopher J. Davis; Carmen R. Hardin; Peter W. C. Paton; et al. (Global Change Biology, 2018)
Species’ distributions will respond to climate change based on the relationship between local demographic processes and climate and how this relationship varies based on range position. A rarely tested demographic prediction is that populations at the extremes of a species’ climate envelope (e.g., populations in areas with the highest mean annual temperature) will be most sensitive to local shifts in climate (i.e., warming). We tested this prediction using a dynamic species distribution model linking demographic rates to variation in temperature and precipitation for wood frogs ( Lithobates sylvaticus ) in North America. Using long‐term monitoring data from 746 populations in 27 study areas, we determined how climatic variation affected population growth rates and how these relationships varied with respect to long‐term climate. Some models supported the predicted pattern, with negative effects of extreme summer temperatures in hotter areas and positive effects on recruitment for summer water availability in drier areas. We also found evidence of interacting temperature and precipitation influencing population size, such as extreme heat having less of a negative effect in wetter areas. Other results were contrary to predictions, such as positive effects of summer water availability in wetter parts of the range and positive responses to winter warming especially in milder areas. In general, we found wood frogs were more sensitive to changes in temperature or temperature interacting with precipitation than to changes in precipitation alone. Our results suggest that sensitivity to changes in climate cannot be predicted simply by knowing locations within the species’ climate envelope. Many climate processes did not affect population growth rates in the predicted direction based on range position. Processes such as species‐interactions, local adaptation, and interactions with the physical landscape likely affect the responses we observed. Our work highlights the need to measure demographic responses to changing climate.

Hydrological Outlook UK: an operational streamflow and groundwater level forecasting system at monthly to seasonal time scales - Christel Prudhomme; Jamie Hannaford; Shaun Harrigan; David Boorman; Jeff Knight; Victoria Bell; Christopher Jackson; Cecilia Svensson; Simon Parry; Nuria Bachiller-Jareno; Helen Davies; Richard Davis; et al. (Hydrological Sciences Journal, 2017)

Relationship between air mass type and emergency department visits for migraine headache across the Triangle region of North Carolina - Christopher Elcik; Christopher M. Fuhrmann; Andrew E. Mercer; Robert E. Davis (International Journal of Biometeorology, 2017)

Drought stress in Pinus taeda L. induces coordinated transcript accumulation of genes involved in the homogentisate pathway - Océane Frelin; Christopher Dervinis; Jill L. Wegrzyn; John M. Davis; Andrew D. Hanson (Tree Genetics & Genomes, 2017)

Heat Survival and Phenotype Microarray Profiling of Salmonella Typhimurium Mutants - Turki M. Dawoud; Anita Khatiwara; Si Hong Park; Morgan L. Davis; Christopher A. Baker; Steven C. Ricke; Young Min Kwon (Current Microbiology, 2017)

Response to varying the nicotine content of cigarettes in vulnerable populations: an initial experimental examination of acute effects - Stephen T. Higgins; Sarah H. Heil; Stacey C. Sigmon; Jennifer W. Tidey; Diann E. Gaalema; Maxine L. Stitzer; Hanna Durand; Janice Y. Bunn; Jeff S. Priest; Christopher A. Arger; Mollie E. Miller; Cecilia L. Bergeria; et al. (Psychopharmacology, 2017)

Leukemia Inhibitory Factor Protects Neurons from Ischemic Damage via Upregulation of Superoxide Dismutase 3 - Stephanie M. Davis; Lisa A. Collier; Christopher C. Leonardo; Hilary A. Seifert; Craig T. Ajmo; Keith R. Pennypacker (Molecular Neurobiology, 2017)

Elevated CO 2 and temperature increase soil C losses from a soybean–maize ecosystem - Christopher K. Black; Sarah C. Davis; Tara W. Hudiburg; Carl J. Bernacchi; Evan H. DeLucia (Global Change Biology, 2017)
Warming temperatures and increasing CO 2 are likely to have large effects on the amount of carbon stored in soil, but predictions of these effects are poorly constrained. We elevated temperature (canopy: +2.8 °C; soil growing season: +1.8 °C; soil fallow: +2.3 °C) for 3 years within the 9th–11th years of an elevated CO 2 (+200 ppm) experiment on a maize–soybean agroecosystem, measured respiration by roots and soil microbes, and then used a process‐based ecosystem model (DayCent) to simulate the decadal effects of warming and CO 2 enrichment on soil C. Both heating and elevated CO 2 increased respiration from soil microbes by ~20%, but heating reduced respiration from roots and rhizosphere by ~25%. The effects were additive, with no heat × CO 2 interactions. Particulate organic matter and total soil C declined over time in all treatments and were lower in elevated CO 2 plots than in ambient plots, but did not differ between heat treatments. We speculate that these declines indicate a priming effect, with increased C inputs under elevated CO 2 fueling a loss of old soil carbon. Model simulations of heated plots agreed with our observations and predicted loss of ~15% of soil organic C after 100 years of heating, but simulations of elevated CO 2 failed to predict the observed C losses and instead predicted a ~4% gain in soil organic C under any heating conditions. Despite model uncertainty, our empirical results suggest that combined, elevated CO 2 and temperature will lead to long‐term declines in the amount of carbon stored in agricultural soils.

Mapping adipose and muscle tissue expression quantitative trait loci in African Americans to identify genes for type 2 diabetes and obesity - Satria P. Sajuthi; Neeraj K. Sharma; Jeff W. Chou; Nicholette D. Palmer; David R. McWilliams; John Beal; Mary E. Comeau; Lijun Ma; Jorge Calles-Escandon; Jamehl Demons; Samantha Rogers; Kristina Cherry; et al. (Human Genetics, 2016)

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

Thermally adaptive tradeoffs in closely related marine bacterial strains - Cheuk‐Man Yung; Marissa K. Vereen; Amy Herbert; Katherine M. Davis; Jiayu Yang; Agata Kantorowska; Christopher S. Ward; Jennifer J. Wernegreen; Zackary I. Johnson; Dana E. Hunt (Environmental Microbiology, 2015)
Summary Time series studies have shown that some bacterial taxa occur only at specific times of the year while others are ubiquitous in spite of seasonal shifts in environmental variables. Here, we ask if these ubiquitous clades are generalists that grow over a wide range of environmental conditions, or clusters of strain‐level environmental specialists. To answer this question, vibrio strains isolated at a coastal time series were phylogenetically and physiologically characterized revealing three dominant strategies within the vibrio: mesophiles, psychrophiles and apparently generalist broad thermal range clades. Thermal performance curves from laboratory growth rate experiments help explain field observations of relative abundances: the mesophilic clade grows optimally at temperatures 16°C higher than the psychrophilic clade. Strains in the broad thermal range clade all have similar optimal growth temperatures but also exhibit temperature‐related tradeoffs with faster growth rates for warm temperature strains and broader growth ranges for strains from cool temperatures. Moreover, the mechanisms of thermal adaptation apparently differ based on evolutionary time scales: shifts in the temperature of maximal growth occur between deeply branching clades but thermal performance curve shape changes on shorter time scales. Thus, apparently ubiquitous clades are likely not generalists, but contain subclusters with distinct environmental preferences.

Computational Modeling of Pathophysiologic Responses to Exercise in Fontan Patients - Ethan Kung; James C. Perry; Christopher Davis; Francesco Migliavacca; Giancarlo Pennati; Alessandro Giardini; Tain-Yen Hsia; Alison Marsden (Annals of Biomedical Engineering, 2015)

Validation of PyMBMS as a High-throughput Screen for Lignin Abundance in Lignocellulosic Biomass of Grasses - Bryan W. Penning; Robert W. Sykes; Nicholas C. Babcock; Christopher K. Dugard; John F. Klimek; David Gamblin; Mark Davis; Timothy R. Filley; Nathan S. Mosier; Clifford F. Weil; Maureen C. McCann; Nicholas C. Carpita (BioEnergy Research, 2014)

Autonomous Ocean Measurements in the California Current Ecosystem - Mark Ohman; Daniel Rudnick; Alexander Chekalyuk; Russ Davis; Richard Feely; Mati Kahru; Hey-Jin Kim; Michael Landry; Todd Martz; Christopher Sabine; Uwe Send (Oceanography, 2013)

Interactions between specific phytoplankton and bacteria affect lake bacterial community succession - Sara F. Paver; Kevin R. Hayek; Kelsey A. Gano; Jennie R. Fagen; Christopher T. Brown; Austin G. Davis‐Richardson; David B. Crabb; Richard Rosario‐Passapera; Adriana Giongo; Eric W. Triplett; Angela D. Kent (Environmental Microbiology, 2013)
Summary Time‐series observations and a phytoplankton manipulation experiment were combined to test the hypothesis that phytoplankton succession effects changes in bacterial community composition. Three humic lakes were sampled weekly M ay– A ugust and correlations between relative abundances of specific phytoplankton and bacterial operational taxonomic units ( OTUs ) in each time series were determined. To experimentally characterize the influence of phytoplankton, bacteria from each lake were incubated with phytoplankton from one of the three lakes or no phytoplankton. Following incubation, variation in bacterial community composition explained by phytoplankton treatment increased 65%, while the variation explained by bacterial source decreased 64%. Free‐living bacteria explained, on average, over 60% of the difference between phytoplankton and corresponding no‐phytoplankton control treatments. Fourteen out of the 101 bacterial OTUs that exhibited positively correlated patterns of abundance with specific algal populations in time‐series observations were enriched in mesocosms following incubation with phytoplankton, and one out of 59 negatively correlated bacterial OTUs was depleted in phytoplankton treatments. Bacterial genera enriched in mesocosms containing specific phytoplankton assemblages included L imnohabitans (clade betI ‐ A ), B dellovibrio and M itsuaria . These results suggest that effects of phytoplankton on certain bacterial populations, including bacteria tracking seasonal changes in algal‐derived organic matter, result in correlations between algal and bacterial community dynamics.

Microbial hitchhikers on intercontinental dust: high-throughput sequencing to catalogue microbes in small sand samples - Adriana Giongo; Jocelyne Favet; Ales Lapanje; Kelsey A. Gano; Suzanne Kennedy; Austin G. Davis-Richardson; Christopher Brown; Andreas Beck; William G. Farmerie; Arlette Cattaneo; David B. Crabb; Yin-Yin Aung; et al. (Aerobiologia, 2013)

Relationship between anthropometric factors, radiation exposure, and colon cancer incidence in the Life Span Study cohort of atomic bomb survivors - Erin O. Semmens; Kenneth J. Kopecky; Eric Grant; Robert W. Mathes; Nobuo Nishi; Hiromi Sugiyama; Hiroko Moriwaki; Ritsu Sakata; Midori Soda; Fumiyoshi Kasagi; Michiko Yamada; Saeko Fujiwara; et al. (Cancer Causes & Control, 2013)

Preoperative sentinel lymph node mapping of the prostate using PET/CT fusion imaging and Ga-68-labeled tilmanocept in an animal model - Sean P. Stroup; Christopher J. Kane; Salman Farchshchi-Heydari; Claude M. James; Christopher H. Davis; Anne M. Wallace; Carl K. Hoh; David R. Vera (Clinical & Experimental Metastasis, 2012)

River inflow, estuarine salinity, and Carolina wolfberry fruit abundance: linking abiotic drivers to Whooping Crane food - Jeffrey R. Wozniak; Todd M. Swannack; Rachel Butzler; Christopher Llewellyn; Stephen E. Davis (Journal of Coastal Conservation, 2012)

Insight in glioma susceptibility through an analysis of 6p22.3, 12p13.33-12.1, 17q22-23.2 and 18q23 SNP genotypes in familial and non-familial glioma - Yanhong Liu; Beatrice S. Melin; Preetha Rajaraman; Zhaoming Wang; Martha Linet; Sanjay Shete; Christopher I. Amos; Ching C. Lau; Michael E. Scheurer; Spiridon Tsavachidis; Georgina N. Armstrong; Richard S. Houlston; et al. (Human Genetics, 2012)

Perfusion/Diffusion Mismatch Is Valid and Should Be Used for Selecting Delayed Interventions - Stephen Davis; Bruce Campbell; Soren Christensen; Henry Ma; Patricia Desmond; Mark Parsons; Christopher Levi; Christopher Bladin; P. Alan Barber; Geoffrey Donnan (Translational Stroke Research, 2012)

Persistent and recrudescent infection in cattle following natural infection with Middle Point orbivirus - Christopher Cowled; Lorna Melville; Richard Weir; Susan Walsh; Aneta Gubala; Steven Davis; David Boyle (Archives of Virology, 2012)

Terrestrial biosphere model performance for inter‐annual variability of land‐atmosphere CO 2 exchange - T.F. Keenan; Ian Baker; Alan Barr; Philippe Ciais; Ken Davis; Michael Dietze; Danillo Dragoni; Christopher M Gough; Robert Grant; David Hollinger; Koen Hufkens; Ben Poulter; et al. (Global Change Biology, 2012)
Interannual variability in biosphere‐atmosphere exchange of CO 2 is driven by a diverse range of biotic and abiotic factors. Replicating this variability thus represents the ‘acid test’ for terrestrial biosphere models. Although such models are commonly used to project responses to both normal and anomalous variability in climate, they are rarely tested explicitly against inter‐annual variability in observations. Herein, using standardized data from the N orth A merican Carbon Program, we assess the performance of 16 terrestrial biosphere models and 3 remote sensing products against long‐term measurements of biosphere‐atmosphere CO 2 exchange made with eddy‐covariance flux towers at 11 forested sites in N orth A merica. Instead of focusing on model‐data agreement we take a systematic, variability‐oriented approach and show that although the models tend to reproduce the mean magnitude of the observed annual flux variability, they fail to reproduce the timing. Large biases in modeled annual means are evident for all models. Observed interannual variability is found to commonly be on the order of magnitude of the mean fluxes. None of the models consistently reproduce observed interannual variability within measurement uncertainty. Underrepresentation of variability in spring phenology, soil thaw and snowpack melting, and difficulties in reproducing the lagged response to extreme climatic events are identified as systematic errors, common to all models included in this study.

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

Genetic diversity of diploid Japanese strawberry species based on microsatellite markers - Wambui Njuguna; Kim E. Hummer; Christopher M. Richards; Thomas M. Davis; Nahla V. Bassil (Genetic Resources and Crop Evolution, 2011)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Mapping Fusarium wilt race 1 resistance genes in cotton by inheritance, QTL and sequencing composition - Mauricio Ulloa; Congli Wang; Robert B. Hutmacher; Steven D. Wright; R. Michael Davis; Christopher A. Saski; Philip A. Roberts (Molecular Genetics and Genomics, 2011)

Restoring Forests and Associated Ecosystem Services on Appalachian Coal Surface Mines - Carl E. Zipper; James A. Burger; Jeffrey G. Skousen; Patrick N. Angel; Christopher D. Barton; Victor Davis; Jennifer A. Franklin (Environmental Management, 2011)

Variation in folate pathway genes and distal colorectal adenoma risk: a sigmoidoscopy-based case–control study - A. Joan Levine; Won Lee; Jane C. Figueiredo; David V. Conti; David J. Vandenberg; Brian D. Davis; Christopher K. Edlund; Susanne M. Henning; David Heber; Mariana C. Stern; Robert W. Haile (Cancer Causes & Control, 2011)

Pacific Atmospheric Sulfur Experiment (PASE): dynamics and chemistry of the south Pacific tropical trade wind regime - Alan Bandy; Ian C. Faloona; Byron W. Blomquist; Barry J. Huebert; Antony D. Clarke; Steven G. Howell; R. L. Mauldin; Christopher A. Cantrell; James G. Hudson; Brian G. Heikes; John T. Merrill; Yuhang Wang; et al. (Journal of Atmospheric Chemistry, 2011)

Cytokinin Primes Plant Responses to Wounding and Reduces Insect Performance - Christopher Dervinis; Christopher J. Frost; Susan D. Lawrence; Nicole G. Novak; John M. Davis (Journal of Plant Growth Regulation, 2010)

Flow effects on benthic grazing on phytoplankton by a Caribbean reef - Stephen G. Monismith; Kristen A. Davis; Gregory G. Shellenbarger; James L. Hench; Nicholas J. Nidzieko; Alyson E. Santoro; Matthew A. Reidenbach; Johanna H. Rosman; Roi Holtzman; Christopher S. Martens; Niels L. Lindquist; Melissa W. Southwell; et al. (Limnology and Oceanography, 2010)
We present measurements of flows and fluxes of phytoplankton to Conch Reef, Florida, a Caribbean reef dominated by sponges and soft corals, located in 15 m of water offshore of Key Largo. Vertical profiles of chlorophyll a, a proxy for phytoplankton biomass, showed a near‐bed depletion, indicating the existence of concentration boundary layers. Along with simultaneous measurements of velocity profiles, near‐bed turbulence, and temperature stratification, these profiles were used to compute α, the mass transfer velocity of phytoplankton to the bed (i.e., the flux to the bed normalized by near‐bed concentration). The α value ranged from ‐40 to +130 m d −1 , with a significant linear positive relationship with shear velocity. The median value of α = 48 ± 20 m d −1 is larger than would be expected, given the observed population of filter‐feeding sponges. Nonetheless, these large values of a are consistent with values found recently for another coral reef as well as for a soft bottom estuarine community. Taken as a whole, these measurements indicate that reefs with large roughness and/or energetic currents should be able to support higher biomasses of benthic organisms than would low relief reefs or reefs in sluggish waters.

The use of aeration as a simple and environmentally sound means to prevent biofouling - Stephan G. Bullard; Sandra E. Shumway; Christopher V. Davis (Biofouling, 2010)

The SUMO conjugation pathway in Populus: genomic analysis, tissue-specific and inducible SUMOylation and in vitro de-SUMOylation - Jon M. Reed; Christopher Dervinis; Alison M. Morse; John M. Davis (Planta, 2010)

Variations in Cellulosic Ultrastructure of Poplar - Marcus Foston; Christopher A. Hubbell; Mark Davis; Arthur J. Ragauskas (BioEnergy Research, 2009)

A hump‐shaped relationship between isolation and abundance of Notonecta irrorata colonists in aquatic mesocosms - Shannon J. McCauley; Christopher J. Davis; Jennifer Nystrom; Earl E. Werner (Ecology, 2009)
We examined the relationship between the isolation of experimental aquatic mesocosms and the abundance of an aquatic insect colonist, Notonecta irrorata , over two years. We used a curve‐fitting approach to assess whether linear or quadratic models better describe the relationship between isolation and abundance. For two measures of mesocosm isolation, distance to nearest source and distance to the largest source population, there was a significant quadratic relationship between isolation and abundance. Abundance of colonizing N. irrorata was not found to be significantly related to a third measure of isolation, mesocosm connectivity. These results indicate that the relationship between habitat isolation and colonist abundance may not be a monotonic decline across all spatial scales, a finding that contradicts the usual assumption incorporated in measures of habitat connectivity. Our results suggest that under some circumstances individuals that have undertaken dispersal may bypass patches they encounter early in this process and preferentially settle in patches encountered later. This behavioral preference in conjunction with decreased numbers of potential colonists at sites far from the source environment could lead to the “hump‐shaped” colonist abundance by habitat isolation relationship we observed in this study. We suggest that simple assumptions about the relationship between habitat isolation and the probability a site is colonized need to be reexamined and alternative possible forms of this relationship tested.

Metacommunity patterns in larval odonates - Shannon J. McCauley; Christopher J. Davis; Rick A. Relyea; Kerry L. Yurewicz; David K. Skelly; Earl E. Werner (Oecologia, 2008)

Evolution and diversity of invertase genes in Populus trichocarpa - Philip N. Bocock; Alison M. Morse; Christopher Dervinis; John M. Davis (Planta, 2008)

Differential contributions of dopaminergic D1- and D2-like receptors to cognitive function in rhesus monkeys - Stefani N. Von Huben; Sophia A. Davis; Christopher C. Lay; Simon N. Katner; Rebecca D. Crean; Michael A. Taffe (Psychopharmacology, 2006)

Wound and insect herbivory responsive genes in poplar - Susan D. Lawrence; Christopher Dervinis; Nicole Novak; John M. Davis (Biotechnology Letters, 2006)

Relating precipitation and water management to nutrient concentrations in the oligotrophic “upside‐down” estuaries of the Florida Everglades - Daniel L. Childers; Joseph N. Boyer; Stephen E. Davis; Christopher J. Madden; David T. Rudnick; Fred H. Sklar (Limnology and Oceanography, 2006)
We present 8 yr of long‐term water quality, climatological, and water management data for 17 locations in Everglades National Park, Florida. Total phosphorus (P) concentration data from freshwater sites (typically −1 , or 8 µg L −1 ) indicate the oligotrophic, P‐limited nature of this large freshwater—estuarine landscape. Total P concentrations at estuarine sites near the Gulf of Mexico (average ~0.5 µmol L −1 ) demonstrate the marine source for this limiting nutrient. This “upside down” phenomenon, with the limiting nutrient supplied by the ocean and not the land, is a defining characteristic of the Everglade landscape. We present a conceptual model of how the seasonality of precipitation and the management of canal water inputs control the marine P supply, and we hypothesize that seasonal variability in water residence time controls water quality through internal biogeochemical processing. Low freshwater inflows during the dry season increase estuarine residence times, enabling local processes to control nutrient availability and water quality. El Ni#x00F1;o—Southern Oscillation (ENSO) events tend to mute the seasonality of rainfall without altering total annual precipitation inputs. The Niño3 ENSO index (which indicates an ENSO event when positive and a La Niña event when negative) was positively correlated with both annual rainfall and the ratio of dry season to wet season precipitation. This ENSO‐driven disruption in seasonal rainfall patterns affected salinity patterns and tended to reduce marine inputs of P to Everglades estuaries. ENSO events also decreased dry season residence times, reducing the importance of estuarine nutrient processing. The combination of variable water management activities and interannual differences in precipitation patterns has a strong influence on nutrient and salinity patterns in Everglades estuaries.

Reduced plantarflexor specific torque in the elderly is associated with a lower activation capacity - Christopher I. Morse; Jeanette M. Thom; Mark G. Davis; Ken R. Fox; Karen M. Birch; Marco V. Narici (European Journal of Applied Physiology, 2004)

Real-Time Data Assimilative Modeling on Georges Bank - Daniel Lynch; Christopher Naimie; Justin Ip; Craig Lewis; Francisco Werner; Richard Leuttich; Brian Blanton; John Quinlan; Dennis McGillicuddy; James Ledwell; James Churchill; Valery Kosnyrev; et al. (Oceanography, 2001)

A survey of unbalanced flow diagnostics and their application - Fuqing Zhang; Steven E. Koch; Christopher A. Davis; Michael L. Kaplan (Advances in Atmospheric Sciences, 2000)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Satellite inventory of human settlements using nocturnal radiation emissions: a contribution for the global toolchest - CHRISTOPHER ELVIDGE; KIMBERLY BAUGH; VINITA HOBSON; ERIC KIHN; HERBERT KROEHL; ETHAN DAVIS; DAVID COCERO (Global Change Biology, 1997)
Time series data from the Defense Meteorological Satellite Program (DMSP) Operational Linescan System (OLS) have been used to derive georeferenced inventories of human settlements for Europe, North and South America, and Asia. The visible band of the OLS is intensified at night, permitting detection of nocturnal visible‐near infrared emissions from cities, towns, and villages. The time series analysis makes it possible to eliminate ephemeral VNIR emission sources such as fire and to normalize for differences in the number of cloud‐free observations. An examination of the area lit (km 2 ) for 52 countries indicates the OLS derived products may be used to perform the spatial apportionment of population and energy related greenhouse gas emissions.

Growth and mortality of cultured bay scallops in the Damariscotta River, Maine (USA) - Bruce J. Barber; Christopher V. Davis (Aquaculture International, 1997)